MOTIVASI INDONESIA DALAM KERJASAMA EKSPOR HOME DECORATION INDONESIA-BELANDA KE EROPA - Robia Saputra; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research discussed Indonesia's motivation in export affiliation of Indonesian-Dutch home decorations to Europe. This research aimed to explain and determine the reasons and the partnership between the two countries to continue expanding export opportunities for Indonesian home decoration products which have abundant potential for raw materials to the European market.  The European market is an appropriate and well-determined in competing, Seeing the suitable market in Europe, making many developing countries also look to this market to export the same product. Thus, it requires that a country must have an understanding of the destination market and good product quality in order to compete and continue to be in demand in the market. Perpective used in this research is mercantilism perspective, and level of analysis used is the nation state.  The theory used in this research is the theory of international cooperation to explain the facts that occur, as well as the data that the author collects from books, journals, articles, websites, and inquires directly through social media to units of the Directorate General of National Export Development of the Ministry of Trade of the Republic of Indonesia. This research showed that it is very important to build collaboration  between Indonesia-Dutch to increase the export of Indonesian home decor products.  Efforts are being made to increase exports and improve the quality of Indonesian products by improving the quality of human resources, understanding the European market, training and guidance, and participating in various exhibitions as a promotional event as well as attracting buyers to open up more export opportunities for home decoration products Indonesia to other countries, especially European countries.Keywords: Export, Home Decoration, European Market, Indonesia-Dutch, Developing Countries.